ANALISIS TREND LIFESTYLE HEALTHY IN FITNESS CENTER (STUDI TENTANG GAYA HIDUP SEHAT DI FITNESS CENTER ROBUST FITNESS KOTA JAMBI) - Muhammad Wildan; Palmizal A; Wawan Junresti Daya (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
Healthy lifestyle in fitness center is increasingly popular among Jambi City community as part of modern lifestyle. This study aims to analyze how healthy lifestyle of robust fitness members, This study uses qualitative approach with in-depth interview method to robust fitness members who actively exercise in robust fitness and robust fitness managers in Jambi City. Data analysis technique used is thematic analysis, where the collected data will be coded with the help of Nvivo12 application and then grouped based on certain themes relevant to the research. The results of the study show that exercising in robust fitness has a contribution in supporting healthy lifestyle. This activity also has a positive impact on improving the health of each individual, such as reducing body fat and reducing the number of non-communicable diseases. To achieve all that, every member who lives a healthy lifestyle must exercise regularly, eat healthy food, and get enough rest. It is hoped that this study can provide practical benefits and become a basis for developing programs or policies that support healthy lifestyle.